1983
DOI: 10.1246/cl.1983.1013
|View full text |Cite
|
Sign up to set email alerts
|

Frontier Orbital Control for the Hydroxyl Radical Attack on Aromatics

Abstract: The ortho:meta:para isomer ratio and p/m value observed in the aromatic hydroxylation with hydroxyl radical in anhydrous organic media are correlated with the electron density of HOMO of aromatics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The OH radical has long been known to be a moderate electrophile, and studies of reactions similar to this involving addition of hydroxyl radicals onto substituted aromatic benzene rings have shown clear electrophilic tendencies in the radical 30. 31 It has been shown that the electron density of the HOMO orbital correlates with the site of hydroxyl radical attack on an aromatic ring 32. Therefore, we have also considered the HOMO and LUMO orbitals, as the present radical reactions with the aromatic rings of the nucleobases are expected to behave in a similar fashion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OH radical has long been known to be a moderate electrophile, and studies of reactions similar to this involving addition of hydroxyl radicals onto substituted aromatic benzene rings have shown clear electrophilic tendencies in the radical 30. 31 It has been shown that the electron density of the HOMO orbital correlates with the site of hydroxyl radical attack on an aromatic ring 32. Therefore, we have also considered the HOMO and LUMO orbitals, as the present radical reactions with the aromatic rings of the nucleobases are expected to behave in a similar fashion.…”
Section: Resultsmentioning
confidence: 99%
“…[30,31] It has been shown that the electron density of the HOMO orbital correlates with the site of hydroxyl radicala ttack on an aromatic ring. [32] Therefore, we have also considered the HOMO and LUMO orbitals, as the present radicalr eactions with the aromatic rings of the nucleobases are expectedt o behavei nasimilarf ashion. We believe that the HOMO orbital of the molecules influence the ease with which an RC is created through interactions of the electrophilicO Hr adical with the most electron-rich part of the HOMO orbitali nt he creation of RCs for both abstractionsa nd additions.…”
Section: Energetics Of the Purine Nucleobasesmentioning
confidence: 99%